PERSEPSI GURU EKONOMI TERHADAP KURIKULUM 2013 EDISI REVISI DI SMA NEGERI BANDA ACEH - Riska Susanti, Sakdiyah, Nazaruddin (Jurnal Economica Didactica, 2019)
ABSTRACTThis study entitled "Persepsi Guru Ekonomi terhadap Kurikulum 2013 Edisi Revisi di SMA Negeri Banda Aceh " aims to know the perception of economics teacher of State Senior High School of Banda Aceh to the Curriculum 2013 revision edition and constraints in its implementation. This research uses qualitative approach with descriptive research type. The subjects of the study were teachers of SMA Negeri 3 Banda Aceh, SMA Negeri 9 Banda Aceh, and SMA Negeri 14 Banda Aceh, while the data source was at SMA Negeri 3 Banda Aceh. There were 2 teachers, SMA Negeri 9 Banda Aceh, there were 3 teachers, and SMA Negeri 14 Banda Aceh has 1 teacher. Techniques used in data collection is library research, field research in the form of observation and interview. Data analysis techniques using techniques in qualitative research that consists of data reduction, data presentation, and conclusion.The results show that the implementation of the revised edition 2013 curriculum is not a problem for the teachers of State Senior High School Banda Aceh, because in terms of the 2013 revised edition of the revision is much simpler, more attitudinal attitudes are done by the subjects teachers of Islamic Education and Pancasila and Citizenship Education , giving the attitudinal value given by the teacher of the subjects of PAI and PPKn sufficiently only noted the development of attitude, in the form of descriptive. Implementation constraints that occur in the curriculum 2013 revised edition faced by SMA Negeri Banda Aceh teacher is a very minimal training, learning resources (books) is not adequate, and not complete the required materials.Keywords : Perception, Curriculum 2013 Revised Edition